2017
DOI: 10.18052/www.scipress.com/ilns.62.35
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Parameter of Palm Oil and Soil from Ihube Community, Okigwe, Imo State Nigeria

Abstract: Abstract. This study assessed the quality of palm oil and soil from Ihube community, Okigwe L.G.A of Imo state in October 2015. The soil samples were collected from the top soil and the palm oil were collected immediately after extraction. Palm oil and soil were analyzed using standard analytical methods and the results obtained were compared to standards. The physicochemical analysis of the soil samples showed that ranges of EC (323.33±0.57-480.33±1.53 us/cm); Moisture Content (MC) ranged from 20.9±0.80 to 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 5 publications
1
25
1
Order By: Relevance
“…Cassava showed not detected for all species of Cr. It was believed that Cr species where bellow detection limit rather than total absence of the metal since researchers [2,37] had earlier detected Cr in the study area. The order of decreasing species concentrations in the studied fruit crops were as follows:…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Cassava showed not detected for all species of Cr. It was believed that Cr species where bellow detection limit rather than total absence of the metal since researchers [2,37] had earlier detected Cr in the study area. The order of decreasing species concentrations in the studied fruit crops were as follows:…”
Section: Discussionmentioning
confidence: 95%
“…Crops grown on soil will reflect the soil health in their products and so soil is a vital tool aspect of agricultural activity [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Microbiological analysis is an important index which could affect the physicochemical properties of palm oil [50][51]. Enyoh and coworkers [5] suggested that microorganisms present in palm oil constitute a major determinant of…”
Section: Quality Of Palm Oil In Imo Statementioning
confidence: 99%
“…Palm oil is an edible oil, reddish in colour derived from the fruits of the oil palm Elaeis guineensis, which is indigenous in West Africa [1][2][3]. The oil palm tree is a perennial tree crop, which produces the highest quantity of oil when compared to other oil producing plants [4][5]. The crop is unique in that it produces two types of oil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation